The Risk Factor of Pregnant Gymnam on The Incidence of Ruptur Perineum in Aliyah Hospital Kendari - Fajar Kurniawan; Julian Jingsung; Abd Gani Baeda; Achyarul Anam; Heriviyatno Julika Siagian (JURNAL KEBIDANAN, 2020)
Perineal rupture is the cause of postpartum maternal hemorrhage, at the Aliyah Hospital in 2016, Perineal rupture amounted to 110 people, in 2017 there were 75 people perineal rupture and in 2018 there were 132 people with perineal rupture. The study aims to analyze the effect of pregnancy exercise with the incidence of ruptured perineum in the post-partum mothers at Aliyah Hospital in Kendari. The study uses case-control design with retrospective approach. The number of sample used 94 people divided into case group as many as 47 respondents and control group as many as 47 respondents.The results of data analysis showing an OR value of 3,527 which means having a risk of 3 (three) times the estimated risk of perineal rupture for those who do not get pregnancy gymnam, where the threshold value is below 1,237 and the threshold value is 10.06 and the value of Chi Square 5,934 X2 Table 3.841. Non-pregnant women who are exercising 3 times are at risk of ruptured perineal rupture during labor.